The cornbread mafia: a homegrown syndicate's code of silence and the biggest marijuana bust in American history - Higdon, James (Lyons Press, 2019)
In the summer of 1987, Johnny Boone set out to grow and harvest one of the greatest outdoor marijuana crops in modern times. By doing so, he set into motion a series of events that defined him and his associates as the largest homegrown marijuana syndicate in American history, also known as "The Cornbread Mafia." The author, whose relationship with Johnny Boone, currently a federal fugitive, made him the first journalist subpoenaed under the Obama administration, takes readers back to the 1970s and '80s and the clash between federal and local law enforcement and a band of Kentucky farmers with moonshine and pride in their bloodlines. By 1989, the task force assigned to take down men like Johnny Boone arrested 69 men and one woman from busts on 29 farms in 10 states, and seizing 182 tons of pot. Of the 70 individuals arrested, zero talked. The who, what, when, where, why and how of it all, is a tale of Mafia-style storylines emanating from the Bluegrass state, and populated by Vietnam veteran and weed-loving characters caught up in violence and heart-breaking altruism. It is accompanied by a soundtrack of Southern rock-and-roll and rhythm-and-blues, and it is told in action-packed, colorful, and riveting detail